Herbal Lepa Formulation Preparation and its Evaluation - Tejaswini Singh, (International Journal of Ayurveda and Pharma Research, 2021)
The concept of beauty is as old as humanity itself. It is the natural desire of every human being to look beautiful and glamorous. The beauty and glamour are because of perfect skin. Herbs have been used for beautification from historic times and have also been described in Ayurvedic literature. Herbs as whole or herbal extracts have been used to treat the various ailments of the skin, hair, body odor, and overall beautification. The demand for Ayurveda in cosmetology is established because it is effective, cheaper, and long-lasting without any side effects. The present study aimed to formulate and evaluate the beneficial effect of herbal Lepa formulation for beautification. Beautification in terms of skin lightening, removal of scars and pigmentation, dark circles, and ultimately healthy glowing skin. The advantage of herbal cosmetics compared to chemical products is they are non-toxic in nature. The Lepa formulation is the suitable dosage form prepared using various natural components in the appropriate and desired quantity for better effectiveness. The formulation has shown significant improvement in various skin problems, including skin pigmentation, melasma, acne marks, and skin lightening effect with no further moisturizing cream requirements.